DINAMIKA KELOMPOK TANI KALELON DI DESA KAUNERAN KECAMATAN SONDER - Emanuel ., Kelbulan; Jane S. Tambas; Oktavianus ., Parajouw (AGRI-SOSIOEKONOMI, 2018)
This study aims to see how the dynamics of the Kalelon farmer groups are examined from the elements of group dynamics. This research took place for 3 months from October to December 2017. The research site was in Kauneran Village, Sonder Sub-district. Data collection techniques carried out in this study were interview techniques. Sample selection using the method purposive sampling. The number of respondents is 15 people who are members of the group. The analysis technique used in this study is a qualitative descriptive analysis technique. The results showed that the Kalelon farmer group was dynamic because of the nine elements of group dynamics consisting of group goals, group structure, group development and coaching, group cohesiveness, group task functions, group atmosphere, group effectiveness, and hidden intentions were dynamic or good dynamic even though there is one element that is not dynamic, namely pressure in the group. *eprm*.